Economies of violence: more oil, more blood - Watts, Michael (2003)
Petroleum in the Nigerian context has produced a combustible politics marked by violence. Rather than see oil-dependency as a source of predation or as a source of state military power, this paper explores how oil capitalism produces particular sorts of enclave economies and governable spaces characterised by violence and instability. While the biophysical qualities of oil matter in this analysis, so do the powers of transnational oil companies, the character of the `the oil complex', and the ways in which oil as a territorially-based and nationalised commodity can become the basis for making claims. - Reproduced.
Keywords: Violence